The Mediation Role of Patient Satisfaction on the Influence of Doctor Competency Quality, Service Quality, and Shared Decision Making on Patient Compliance Toward Surgery Recommendations at Eka Hospital, Bekasi - Andry Giovanny; Oscar Jayanagara (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the influence of Doctor Competence Quality, Service Quality, and Shared Decision Making (SDM) on Patient Satisfaction, as well as the impact of Patient Satisfaction on Patient Compliance at Eka Hospital Bekasi, with a focus on the mediating role of Patient Satisfaction. Data were collected from 125 respondents using a quantitative approach and analyzed through Partial Least Squares - Structural Equation Modelling (PLS-SEM). The findings reveal that Service Quality and Shared Decision Making significantly and positively influence Patient Satisfaction, whereas Doctor Competence Quality does not exert a significant effect. Moreover, Patient Satisfaction positively and significantly influences Patient Compliance. The mediating role of Patient Satisfaction is significant only in the relationship between Shared Decision Making and Patient Compliance, while it is not significant in the relationships involving Doctor Competence Quality and Service Quality. These findings underscore the critical role of engaging patients in shared medical decision-making processes to enhance satisfaction and compliance, while further research is warranted to explore the contributions of service quality and doctor competence in fostering patient compliance.